Comparing Outcomes of Competitive Athletes Versus Nonathletes Undergoing Hip Arthroscopy for Treatment of Femoroacetabular Impingement Syndrome. Issue 1 (January 2020) - Clapp, Ian M.; Nwachukwu, Benedict U.; Beck, Edward C.; Jan, Kyleen; Gowd, Anirudh K.; Nho, Shane J.
Background: A growing number of studies have examined return to sport in competitive athletes after undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS); however, few have evaluated the rate of achieving meaningful clinical outcomes in this group. Purpose: To determine if competitive athletes (professional, semiprofessional, or collegiate) have better 2-year patient-reported outcomes and achieve the minimal clinically important difference (MCID) and substantial clinical benefit at higher rates when compared with nonathletes undergoing hip arthroscopy for the treatment of FAIS. Study Design: Cohort study; Level of evidence, 3. Methods: The study was a retrospective analysis of all consecutive patients who identified as either a competitive athlete or a nonathlete and had undergone hip arthroscopy for FAIS by a single fellowship-trained surgeon between January 2012 and April 2017. Patients in the 2 groups were matched 1:2 by age, sex, and body mass index. Baseline and clinical outcomes, including the Hip Outcome Score–Activities of Daily Living, Hip Outcome Score–Sports Subscale (HOS-SS), modified Harris Hip Score, and international Hip Outcome Tool-12, were collected preoperatively and at 2 years postoperatively and compared between the groups. The MCID and substantial clinical benefit were calculated for each group separately and compared using chi-square analysis. Results: A total of 59 competitive athletes and 118 nonathletes were included in the final analysis. Most of the competitive athletes were soccer players (23.7%), followed by softball players (10.2%) and runners (10.2%). Postoperative score comparison between competitive athletes and nonathletes demonstrated a statistically significant difference in the HOS-SS (mean ± SD, 84.5 ± 19.0 vs 76.1 ± 23.8; P = .02). Meaningful outcome analysis demonstrated that competitive athletes had a higher rate of achieving the HOS-SS threshold for the MCID (97.4% vs 82.5%; P = .021). There was no other difference in frequency of achieving the threshold for any other meaningful clinical outcome between the groups. Conclusion: Hip arthroscopy for the treatment of FAIS in competitive athletes and nonathletes produced clinically meaningful outcomes in both patient groups. However, competitive athletes achieved the MCID on the HOS-SS at higher rates than nonathletes and had significantly higher scores at 2 years postoperatively on the HOS-SS.